Migrant Perceptions of Criminal Justice Systems: A Comparative Study of U.S. and Home Country Systems - Fei Luo; John C. Kilburn (Social Sciences)
Background: The United States has the highest number of immigrants in the world, with over 46 million foreign-born residents as of 2022. A growing number of migrants originate from Latin America, driven by factors such as economic instability, food insecurity, and crime. This study explores their experiences and perceptions regarding trust in the criminal justice system (CJS) in both their home countries and the United States. Methods: This study surveyed 500 migrants at a transitional institution in a U.S.–Mexico border city in the summer of 2023. The survey assessed confidence in law enforcement, immigration officers, courts, and government institutions using a 5-point Likert scale. Results: Migrants reported significantly higher confidence in the U.S. CJS compared to that of their home countries. Multivariate analysis revealed that satisfaction with border officials, documentation status, English proficiency, and health were positively associated with confidence in the U.S. CJS, while employment status, traveling with family, and fear of crime correlated with lower confidence. Conclusions: This study highlights the stark contrast in migrants’ confidence levels between their home countries and the U.S. criminal justice system. While migrants view the U.S. system as more legitimate, challenges such as fear of crime and legal uncertainties persist.